Differential germination response of Navua sedge (Cyperus aromaticus) populations to environmental factors. Issue 6 (27th November 2021) - Chauhan, Bhagirath S.
Abstract: Navua sedge [ Cyperus aromaticus (Ridl.) Mattf. & Kuek.], is a hard to control C4 perennial weed species in tropical regions of Australia. Knowledge of its seed biology could help to develop integrated weed management programs for this species. This study was conducted under laboratory and screenhouse conditions to evaluate the effect of alternating day/night temperatures, light, pretreatment high temperatures, burial depth, and flooding depth on the germination and emergence of two populations (Ingham and Tablelands) of C. aromaticus . Both populations germinated at temperatures ranging from 20/10 to 35/25 C; however, the Ingham population germination (76%) was greater than the Tablelands population (42%) at the highest temperature regime (35/25 C). None of the populations germinated at 15/5 C. Darkness completely inhibited germination in both populations, suggesting that the seeds are positively photoblastic. Seeds (dry and wet) of both populations germinated after exposure to pretreatment temperatures of up to 100 C for 5 min. After pretreatment at 150 C, only the Ingham population germinated, and germination was greater for dry seeds (62%) than for wet seeds (1%). Neither population germinated after exposure to 200 C. For both populations, maximum germination was observed for seeds at 0 cm; a burial depth of 0.5 cm completely inhibited emergence of the Tablelands population, and a burial depth of 2.0 cm completely inhibited germination of the Ingham population. A flooding depth of 10 cm greatly reduced emergence in both populations compared with 0 cm (62% and 78%) but 12% to 14% of seedlings still emerged, suggesting the need to integrate flooding with other management tools. The results also suggest that the Ingham population may have a greater potential to spread into new areas or become more invasive than the Tablelands population. Knowledge gained from this study can be used to manage C. aromaticus by fire/burning, tillage, and flooding.